The sexual politics of gendered violence and women's citizenship - Franzway, Suzanne; Moulding, Nicole; Wendt, Sarah; Zufferey, Carole; Chung, Donna (Policy Press, 2019)
This book examines how responses by the state shape a woman's citizenship long after she has escaped from a violent partner. It investigates the effects of intimate partner violence on everyday life including housing, employment, mental health and social participation, and offers critical insights for the development of social policy and practice